2019
DOI: 10.3390/nano9081083
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in Photoelectrochemical Performance of Optimized Amorphous SnS2 Thin Film Fabricated through Atomic Layer Deposition

Abstract: Two-dimensional (2D) nanomaterials have distinct optical and electrical properties owing to their unique structures. In this study, smooth 2D amorphous tin disulfide (SnS2) films were fabricated by atomic layer deposition (ALD), and applied for the first time to photoelectrochemical water splitting. The optimal stable photocurrent density of the 50-nm-thick amorphous SnS2 film fabricated at 140 °C was 51.5 µA/cm2 at an oxygen evolution reaction (0.8 V vs. saturated calomel electrode (SCE)). This value is bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…The generated photocurrent was up to eight times higher compared to bare SnS 2 and 19 times higher than that of bare AZO device (Figure 15c). Hu et al [249] also reported SnS 2 /FTO electrodes that could be used as either photocathode or photoanode, as described in the previous section.…”
Section: Photoelectrocatalytic Water Splittingmentioning
confidence: 96%
See 3 more Smart Citations
“…The generated photocurrent was up to eight times higher compared to bare SnS 2 and 19 times higher than that of bare AZO device (Figure 15c). Hu et al [249] also reported SnS 2 /FTO electrodes that could be used as either photocathode or photoanode, as described in the previous section.…”
Section: Photoelectrocatalytic Water Splittingmentioning
confidence: 96%
“…Using SnS 2 films deposited on FTO‐coated glass, Hu et al. [ 249 ] achieved both PEC HER (photocathode) and PEC OER (photoanode) under acidic conditions (0.25 m H 2 SO 4 ). However, the maximum current densities were relatively low, 35.1 and 51.5 µA cm −2 for HER and OER at −0.4 and +1.0 V, respectively.…”
Section: Applications Of Atomic Layer Deposited 2d Metal Dichalcogenidesmentioning
confidence: 99%
See 2 more Smart Citations
“…MoS 2 deposited on CdS nanorods, [ 49 ] and SnS 2 deposited as an amorphous film. [ 50 ] Both procedures applied H 2 S as a precursor for sulfide, dissolved in an inert carrier gas. Regardless of the material and deposition procedure, thermal annealing is necessary for all ALD‐deposited light absorbers.…”
Section: Light Absorbermentioning
confidence: 99%